Psychometric evaluation of the Multidimensional Health Locus of Control scales in Englishand Spanish-speaking Hispanic Americans - Garcia-Alcaraz, Cristian; Mills, Sarah; Roesch, Scott C.; Sadler, Georgia Robins; Malcarne, Vanessa L.; ATASEVEN, BURÇİN (My University, 2020)
The English and Spanish versions of the Multidimensional Health Locus of Control scales have not been psychometrically evaluated for use with Hispanic Americans. Hispanic American adults (N = 436) completed the English (n = 210) or Spanish (n = 226) Multidimensional Health Locus of Control scales. A multiple-group confirmatory factor analysis did not support equivalent four-factor structures for Spanish- and Englishspeaking Hispanic Americans. Follow-up exploratory factor analyses of the 24 items supported an 18-item, four-factor structure for English-speaking Hispanic Americans and a 22-item, three-factor structure for Spanish-speaking Hispanic Americans. These results suggest caution when using the Multidimensional Health Locus of Control scales with Hispanic Americans.
Keywords: Health locus of control; Hispanic Americans; Multidimensional Health Locus of Control scales; Spanish